Identifikasi, Tahapan, dan Dampak Konflik Pada Lembaga Pendidikan Di MIS Al-Hidayah Kaliwates - Wardatun Nadziro; Muzayyanah Agustin; Mutia Zahrani; Mu'alimin Mu'alimin (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
Education has a crucial role in shaping a proactive and holistic learning environment. This article discusses internal conflicts that arise in Madrasah Ibtidaiyah (MI) Al-Hidayah regarding differences in views on education policies and teaching methods. These conflicts involve different interpretations of vision and mission, resistance to policy change, and interpersonal conflicts among administrators, teachers, and parents. The stages of conflict start from disagreement, involve resolution efforts, and have an impact on individual relationships and institutional performance.In a theoretical context, this article highlights the history of MI as the first Islamic educational institution in Indonesia and how MI teaches conflict identification skills as an integral part in the character building of learners. The research method used was descriptive qualitative with MI Al-Hidayah as the research subject. Data analysis involves collecting, reducing, presenting, and inferring data, providing deep insight into the sources, stages, and impacts of conflict in MI Al-Hidayah.